2020
DOI: 10.1101/2020.07.09.195552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Female mice exposed to low-doses of dioxin during pregnancy and lactation have increased susceptibility to diet-induced obesity and diabetes

Abstract: AbstractAim/hypothesisPersistent organic pollutants have consistently been associated with increased diabetes risk in humans. However, very few studies have assessed the risk of chronic low-dose exposure to pollutants during pregnancy. We investigated the short- and long-term impact of chronic low-dose dioxin exposure during pregnancy and lactation on glucose homeostasis and beta cell function in female mice, including their response to a meta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…We have reported induction of Cyp1a1 in mouse and human islets following direct exposure to TCDD/dioxin or dioxin-like pollutants in vitro and in mouse islets following systemic administration of TCDD in vivo ( 73 ). Moreover, in pregnant TCDD-exposed mice, Cyp1a1 was induced 17-fold in pancreas compared to only 3-fold and 7-fold in liver and adipose, respectively ( 74 ). Therefore, pancreatic cells are not only directly exposed to pollutants in vivo , but may even act as a “sink” for long-term storage of lipophilic chemicals, similar to adipose depots.…”
Section: Toxicity Testing In Pancreatic β-Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported induction of Cyp1a1 in mouse and human islets following direct exposure to TCDD/dioxin or dioxin-like pollutants in vitro and in mouse islets following systemic administration of TCDD in vivo ( 73 ). Moreover, in pregnant TCDD-exposed mice, Cyp1a1 was induced 17-fold in pancreas compared to only 3-fold and 7-fold in liver and adipose, respectively ( 74 ). Therefore, pancreatic cells are not only directly exposed to pollutants in vivo , but may even act as a “sink” for long-term storage of lipophilic chemicals, similar to adipose depots.…”
Section: Toxicity Testing In Pancreatic β-Cellsmentioning
confidence: 99%
“…Additionally, we and others have shown that dioxin suppresses insulin secretion in rodent islets ( 73 , 79 , 80 ) and human islets ( 73 ). Interestingly, acute high-dose dioxin exposure caused β-cell apoptosis in male mice but not female mice ( 81 ), whereas prolonged low-dose dioxin exposure led to impaired β-cell adaptation to high fat diet feeding in female but not male mice ( 74 , 82 ).…”
Section: Toxicity Testing In Pancreatic β-Cellsmentioning
confidence: 99%